Analisis Kelayakan Finansial Usaha Pengolahan Sagu di Kelurahan Labibia Kecamatan Mandongakota Kendari - Patriawan, Wandi; Geo, Laode; Zani, Munirwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
The purpose of this research is to know the process of sago starch processing at Sago Meohai Group business, second what are the facilities used in sago starch processing and the third to know the financial feasibility of sago processing business in Labibia Subdistrict of Mandonga Subdistrict Kendari City (case study on the business Sago Meohai Group). The analysis used in this research is Financial Feasibility Analysis which consist of Net Present Value (NPV), Net Benefit Cost Ratio (NBCR), Internal Rate of Return (IRR), Payback Period (PBP) and Sensitivity Analysis. The results of this study show that the process of sago starch processing in the Meohai Sago Group Enterprises is still simple even though the process of processing has been using a solvent, senso machine, water machine and solvent machine, but in other processes still done by humans. Facilities and Infrastructure used in the processing of sago starch such as land, solvent, water machine, senso and solvent are all in good condition, only the road to the research location is in poor condition because it is still dominated by land and weeds. Meanwhile, in terms of feasibility Business Group Sagu Meohai feasible to cultivate. Due to discount factor (df) 9.1%, obtained NPV value of Rp 98.133.361, NBCR of 9.71, IRR of 172.93%. and PBP 0,56 years or 6 months 21 days with age of 11 years whereas feasibility feasibility analysis where if condition of increase of operational cost equal to 6,57% at discount factor (df) 9.1%, obtained NPV value equal to Rp 56.068.996, NBCR 5.55, IRR of 109.9%, and PBP of 0.84 years or 10 months 2 days whereas if the selling price decreased by 6.57% at the discount factor (df) 9.1%, obtained NPV value of Rp 48.973. 432, NBCR of 4.84, IRR of 97.9% and PBP of 0.93 years or 11 months 4 days. In such circumstances Sago Meohai Group Business is still feasible to cultivate